Analisis prinsip desain sustainable fashion upcycle pada busana kasual - Listiani, Sri; Zahra, Eneng Lutfia; Suryawati, Suryawati; Danial, Mohamad Ikbal Riski A. (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
The development of the fashion industry is influenced by rapid trend changes from time to time. This rapid change in trends ultimately gave rise to the fast fashion industry with the ready-to-wear concept, resulting in fashion products at low prices and produced in large quantities and quickly. This phenomenon has become a new problem in the fashion industry, namely the large amount of fashion waste produced, resulting in environmental pollution due to non-degradable waste. This problem can be overcome by starting education through fashion enthusiasts. The purpose of this study is to create casual clothing from upcycle results and evaluate it through aesthetic design principles. The method used is descriptive qualitative method. Data obtained through primary data and secondary data. Primary data was obtained from structured interviews with expert panelists while secondary data was obtained from the results of a literature review. The data obtained is then studied further to determine the aesthetic assessment of uocycle products based on design principles. The results obtained from this research are that all products created have implemented design principle indicators so that they meet the product indicators that have aesthetic value in the appearance of design principles.